Trade Liberalization and Poverty: The Evidence So Far - Winters, L. Alan; McCulloch, Neil; McKay, Andrew (Journal of Economic Literature, 2004)
This paper assesses the current state of evidence on the impact of trade policy reform on poverty in developing countries. There is little empirical evidence addressing this question directly, but a lot of related evidence on specific aspects. We summarize this evidence using an analytic framework addressing four key areas: economic growth and stability; households and markets; wages and employment and government revenue. Twelve key questions are identified and empirical studies and results are discussed. We argue that there is no simple generalizable conclusion about the relationship between trade liberalization and poverty, and the picture is much less negative than is often suggested. In the long run and on average, trade liberalization is likely to be strongly poverty alleviating, and there is no convincing evidence that it will generally increase overall poverty or vulnerability. But there is evidence that the poor may be less well placed in the short run to protect themselves against adverse effects and take advantage of favorable opportunities.